Argon Laser Photoablation for Postburn Conjunctival Pigmentation - Seong Joon Ahn; Jae Hoon Jeong; Hyo Jong Cho; Dong-Hoon Lee; Hyun Chul Kim (Case Reports in Medicine)
We report a case of an ocular burn injury from boiling water which resulted in conjunctival pigmentation, 1 week following injury. For cosmetic purposes, 2 sessions of argon laser photoablation were performed. One month after laser treatment, conjunctival pigmentation had been successfully removed and the patient was very satisfied with the results. Argon laser photoablation may be an effective way to remove postburn conjunctival pigmentation.